Managing transition in Yemen: An assessment of the costs of conflict and development scenarios for the future - Breisinger, Clemens; Ecker, Olivier; Al-Riffai, Perrihan; Engelke, Wilfried; Al-Bataly, Abdulmajeed (International Food Policy Research Institute, 2012)
This paper has been produced to support the Government of Yemen and the international community in designing a transition plan for the country. The political crisis and conflict situation in Yemen has led to a sharp decline in economic output beginning in 2011—a decline from which Yemen is estimated to recover only in 2015, if favorable conditions apply. Moreover, the impact of the crisis on the poor is dramatic